Human-Machine Cooperative Marine Lifting Of Slender-Beam Payload With A Multi-Tagline Anti-Sway And Positioning System - Sun Maokai; Wang Shenghai; Han Guangdong; Chen Haiquan; Sun Yuqing (Polish Maritime Research)
To address the challenges of low positioning efficiency, difficulty, and high risk in the hoisting and positioning of a slender-beam payload (SBP) under rough sea conditions, a human-machine cooperative lifting method (HMCLM) is proposed for the first time. In this approach, the operator collaborates with a multi-tagline anti-sway and positioning system (MTAPS) to achieve the rapid and precise positioning of the SBP. A dynamic model of the MTAPS is developed based on multibody dynamics and classical Newtonian mechanics; it also considers the operator’s safety requirements. Simulation analysis is conducted using MATLAB/Simulink, and the results indicate that the HMCLM achieves approximately a 10% improvement in sway reduction compared to the MTAPS. Furthermore, the experimental results demonstrate that the MTAPS achieves an average sway reduction of 89.7% for the double-pendulum system. The proposed HMCLM enables the rapid and precise offshore positioning of the SBP, offering a novel approach to enhancing the efficiency of offshore hoisting operations.